Peter Stalker, The Work of Strangers : A Survey of International Labour Migration. Ginebra, International Labour Office, 1994 - Castillo, Manuel Ángel (Estudios Demográficos y Urbanos, 1999)
Peter Stalker, The Work of Strangers: A Survey of International Labour Migration, Ginebra, International Labour Office, 1994.